1998
DOI: 10.1086/517431
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus C/Hepatitis G Virus Infection: A Favorable Prognostic Factor in Human Immunodeficiency Virus—Infected Patients?

Abstract: To investigate a possible influence of GB virus C (GBV-C) in immunocompromised patients, the prevalences of GBV-C RNA and anti-E2 antibody in 197 human immunodeficiency virus (HIV)-infected patients and in 120 control blood donors were studied. GBV-C RNA was detected in 33 of 197 HIV-infected patients (16.8%) compared with 1 in 120 blood donors (0.8%) (P < .001). Previous exposure to GBV-C (anti-E2 antibody-positive) was shown in 56.8% of HIV patients and in 9% of blood donors. GBV-C viremia was not associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
3
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 14 publications
8
111
3
5
Order By: Relevance
“…The discovery in 1998 of the possible benefit to survival and slowing of progression to AIDS among HIV infected patients who are co-infected with GBV-C [Heringlake et al, 1998] provided renewed interest in the seemingly harmless GB virus C [Alter et al, 1997;Alter, 2004]. Numerous studies reported a protective effect of GBV-C and HIV co-infection, though a few studies have observed no effect [Tillmann and Manns, 2001;Stapleton et al, 2004].…”
Section: Biological Relevance Of Gbv-c Genotypesmentioning
confidence: 99%
“…The discovery in 1998 of the possible benefit to survival and slowing of progression to AIDS among HIV infected patients who are co-infected with GBV-C [Heringlake et al, 1998] provided renewed interest in the seemingly harmless GB virus C [Alter et al, 1997;Alter, 2004]. Numerous studies reported a protective effect of GBV-C and HIV co-infection, though a few studies have observed no effect [Tillmann and Manns, 2001;Stapleton et al, 2004].…”
Section: Biological Relevance Of Gbv-c Genotypesmentioning
confidence: 99%
“…The beneficial effect of the co-infection by the GBV-C/HGV in HIVinfected subjects has been under intense scrutiny and debate over the last few years, after the first demonstration of its protective role by several research groups around the world 6,9,21 . Several studies corroborated these findings 23 while a few others failed to substantiate them 22 .…”
Section: Introductionmentioning
confidence: 99%
“…During co-infection of these viruses, progression to AIDS is delayed in some individuals, 10 mortality rate is reduced and longer survival rates observed once AIDS has developed. [11][12][13][14] However, other studies did not report these effects probably due to the different stages of AIDS in the study populations. [15][16][17] In addition, these viruses may have an African origin, 18 but show different degrees of fitness in primates.…”
Section: Introductionmentioning
confidence: 75%